Self-Control of Social Media Usage in Adolescents - Aulia Nurhanifa; Efri Widianti; Ahmad Yamin (Persatuan Perawat Nasional Indonesia (PPNI) Jawa Tengah, 2020)
Social media being the most frequently accessible to all the community, especially teenagers. Teenangers being more susceptible to the negative impact of social media because the limitation of their self-regulation. So, self-control to be the one important factor that can be strongly influence the behavior of social media usage in adolescents. The purpose of this study was identify sel-control of social media usage in adolescents at SMAN 10 Bandung. This type of research is quantitative with descriptive method. The samples recruited in this study were class XI students who have social media applications on their smartphones and use SKS learning system with using a total sampling technique (n=286, response rate 67,6%). Data collection using a modified Self Control Scale by Rika (2012) and Self-Control theory by Averil with validity values between 0.424-0.778 and alpha Cronbach coefficient 0.919. The instrument consists of 27 statement items using a 1 – 5 Likert scale. Data analysis used frequency distribution and percentage. The result of the research showed that 66,8% of teenagers at SMAN 10 Bandung had moderate self-control of social media usage, the largest percentage of participants had high cognitive control (62,9%), moderate decisional control (81,8%) and moderate behavioral control (76,2%). The conclusion of this research that the largest percentage of participants had moderate sel-control of social media usage which meant that participants have not maximized their self control abilities and have the potential to lead to low or high self control.